Ritual Communication Mungka Traditions In Tepal Village Sumbawa Regency - Aswar Tahir; Aka Kurnia SF; Vivin Nila Rakhmatullah; Nadira Jaya Setiawan; Siska Mandalia (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2024)
Culture is one of Indonesia's wealth. The role of the community, especially indigenous peoples in Indonesia, is to preserve the culture inherited from ancestors so that it is not lost in the modernization era. In this case, the importance of younger generation, as the successor of the nation, knows the meaning of a tradition so that it becomes part of the preservation of culture itself. The purpose of this study was to find out the message contained in the communication of Mungka trade rituals in Tepal Village, Sumbawa Regency. The method used in this study is qualitative descriptive. The data collection technique used is with primary and secondary data. In determining informants in this study, researchers used purposive sampling techniques. The results of this study show that the message in the Mungka traditional tradition is not just a symbol of the maturation process. But it holds a deep meaning apart from the symbol of maturity. The traditional procession is expected to be a procession that makes the people of Tepal Village become responsible humans and respect the cultural values taught by the ancestors, with the increased responsibility expected by every community.